Opportunities to sustain matricentric models of community and person-centered care for perinatal substance use in the post Dobbs Deep South - Moss, Regan A.; Locke, Emily; Injeian, Arianna; Hall, Kelli Stidham (Frontiers in Psychiatry, 2025)
Substance use during pregnancy is a growing public health concern, in part due to increasing rates of pregnancy criminalization that are heavily concentrated in the United States (US) Deep South. While existing public health models of care are designed to address substance use during pregnancy, these models often center the fetus rather than the pregnant/birthing person. We argue that patient and community centered models of care are needed to ensure pregnant people who use substances have access to respectful and safe care. We identify person-centered and community-care models for birthing people that rehumanize the birthing person and transform their subjectivity, moving from an object of medical intervention to a collaborator in their own care. By integrating matricentric feminist framings with the Dynamic Sustainability Framework (DSF) we build on theorizations of person-centered care to further invert the medical gaze, resist the governing of pregnant bodies, and proactively prevent self and other regulation of birthing persons. In doing so, we identify opportunities to sustain community-centered peer support specialist, substance use doula, and peer support group care models into the unique cultural contexts, healthcare settings, and policy climates of the post-Dobbs Deep South.